PENGENALAN DIGITAL MARKETING DALAM MENINGKATKAN PENGHASILAN IBU PEMBINAAN KESEJAHTRAAN KELUARGA (PKK) DI DESA TAPIS - Nuraini, Nuraini; Prihatin, Titiek Aryati; Ramadhan, Fathur Rahman; Noor, Jelita Miranda; Annisa, Rabiatul (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Digital marketing is a marketing strategy that utilizes digital platforms to promote products or services to consumers. In the era of technology that continues to develop, digital marketing is one of the most effective and efficient methods in reaching the target market widely and quickly. One of the things that can increase sales is social media. The purpose of holding community service is to introduce digital marketing to PKK women in Tapis Village by providing socialization and digital marketing training. From the results of the discussion we got, the business run by PKK mothers was less than optimal because the only people who knew about their business were local residents who had not used online media in product marketing. Therefore, we carry out community service to provide socialization in the form of digital marketing to PKK mothers to increase sales of the products they produce. Keywords: digital marketing, PKK mother, social media